1987
DOI: 10.1021/ic00257a013
|View full text |Cite
|
Sign up to set email alerts
|

Solvolysis reactions of cis- and trans-diamminedichloroplatinum(II) in dimethyl sulfoxide. Structural characterization and DNA binding of trans-bis(ammine)chloro(DMSO)platinum(1+)

Abstract: observed in the resulting product mixture were [PtC12(dmpe)], cis-[PtC12(PPh3)2], and [Pt(dmpe)2]C12. No evidence for the cationic complex [PtCl(PPh,)(dmpe)]+ was obtained.Reaction of [PH)12(dmpe)l with PMePb2. (a) [PtCMdmpe)] (0.037 g, 0.088 mmol) was mixed with CDCI, in a 5-mm NMR tube. After the tube had been flushed with argon, PMePh, (16.3 pL, 0.088 mmol) was added. 3'P(1HJ NMR analysis of the resulting mixture indicated that the predominant platinum-containing species was [PtC1(PMePhz)(dmpe)]C1.(b) When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
38
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 1 publication
7
38
0
1
Order By: Relevance
“…The PtÐCl bond cis to the dimethyl sulfoxide (dmso) ligand is slightly shorter than the trans-PtÐCl bond, in line with the trend generally observed for ligands with a trans in¯uence. While the PtÐS distance is within the range reported for other Pt II ±sulfoxide derivatives (Pasini et al, 1994;Sundquist et al, 1987), it is noteworthy that this bond length of 2.220 (3) A Ê is greater than the value expected when considering the cis in¯uence of related ligands (Belsky et al, 1991). This is likely to be due to the electron-donating ability of the methoxy group in the 2-position of the ring.…”
supporting
confidence: 51%
See 2 more Smart Citations
“…The PtÐCl bond cis to the dimethyl sulfoxide (dmso) ligand is slightly shorter than the trans-PtÐCl bond, in line with the trend generally observed for ligands with a trans in¯uence. While the PtÐS distance is within the range reported for other Pt II ±sulfoxide derivatives (Pasini et al, 1994;Sundquist et al, 1987), it is noteworthy that this bond length of 2.220 (3) A Ê is greater than the value expected when considering the cis in¯uence of related ligands (Belsky et al, 1991). This is likely to be due to the electron-donating ability of the methoxy group in the 2-position of the ring.…”
supporting
confidence: 51%
“…Compound (I) is a square-planar Pt derivative with bond distances and angles at the Pt atom in the normal range (Sundquist et al, 1987;Melanson & Rochon, 1977b). The Pt atom deviates by 0.012 (1) A Ê from the mean plane of the ligand atoms (NÐSÐCl1ÐCl2).…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…concentration 7.5 mM) and then dissolved in the complete culture medium, at concentrations twice those of the final ones, and 1 mL of resulting solution was added per well. The solutions of 2 and CDDP compounds were freshly made before every experiment to avoid the solvolysis [53,54]. Stock solution of 1 was stored refrigerated.…”
Section: Solution Stability Studies: Uv-vis Spectroscopymentioning
confidence: 99%
“…In regard to the dppf containing complexes this assumption is based on a study by Longato et al, 20 in which it was found that for Pt(dppf)Cl 2 (complex I) dissolved in neat DMSO the mono-substituted DMSO product formed only on addition of AgBF 4 and the bis product did not form at all. In the case of cisplatin (complex IV) the first-order rate constant of solvolysis in neat DMSO has been determined as 6.24 × 10 −5 s −1 at 26 • C. 21 Since the solutions of all complexes were freshly prepared for each measurement, the time spent in neat DMSO prior to addition to aqueous solution was less then five minutes (corresponding to less than 3% conversion of cisplatin to the solvolysis product).…”
Section: Kinetic Measurements In Aqueous Solutionmentioning
confidence: 99%